From peace and the planetary republics of the century of lights to the materialization of perpetual peace and universal citizenship (2020)
In this article, the author examines the relationship between the integration of people and peace from the perspective of the planetary republics of the century of lights and the consolidated experiences of the United States and the European Union. The methodology use is a documentary and bibliographical review and critical analysis, through which the author discusses the evolution of integrationist ideas related to peace and to the possibilities of its universalization through public international law. The main conclusion is that the consolidated experiences show that the harmonious integration of nations entails the foundations of perpetual peace.